Burning velocities of DME(dimethyl ether)-air premixed flames at elevated temperatures. (1st May 2017) - Varghese, Robin John; Kishore, V. Ratna; Akram, M.; Yoon, Y.; Kumar, Sudarshan
Abstract: This paper reports the measurement of laminar burning velocities of DME (dimethyl ether)-air mixtures at higher mixture temperatures using planar flames stabilized in a controlled temperature mesoscale diverging channel. The reliability of this technique for flame speed measurement at high mixture temperatures has been established through various numerical studies using detailed 3-D computational model for DME-air mixtures. The distribution of fuel-air mass flux, reaction zone, and flame shape indicate that a planar flame is indeed formed in both transverse and depth directions of the channel. The stabilized flame is independent of any stretch effects except mild hydrodynamic strain due to channel divergence (30-50 s −1 ), and measured values of laminar burning velocities are within ±5% of the actual value. The experiments were carried out at various equivalence ratios (ϕ = 0.7–1.4) and elevated mixture temperatures (350–640 K). The burning velocities and temperature exponents were determined using the planar flames stabilized at different mixture inlet velocities and temperatures. Slightly rich mixtures (ϕ = 1.1) point to the maximum burning velocity, in good agreement with recent literature at ambient conditions. Temperature exponents for different equivalence ratios increase to both sides of ϕ = 1.1. Numerically calculated laminar burning velocities with different chemical kinetic schemes compared well with the measured burning velocities at higher mixture temperatures. Highlights: Burning velocities of DME-air mixtures measured using diverging mesoscale technique. Burning velocity extracted from flat flames stabilized in a preheated diverging channel. Burning velocity correlations are presented for higher mixture temperatures. Maximum burning velocity observed for slightly rich mixtures at higher temperatures. Variation of burning velocity and temperature exponent (α)matches with predictions.